EBR1 genomic expansion and its role in virulence of Fusarium species. (12th December 2013) - Jonkers, Wilfried; Xayamongkhon, Henry; Haas, Matthew; Olivain, Chantal; van der Does, H. Charlotte; Broz, Karen; Rep, Martijn; Alabouvette, Claude; Steinberg, Christian; Kistler, H. Corby
Summary Genome sequencing of Fusarium oxysporum revealed that pathogenic forms of this fungus harbour supernumerary chromosomes with a wide variety of genes, many of which likely encode traits required for pathogenicity or niche specialization. Specific transcription factor gene families are expanded on these chromosomes including the EBR1 family (Enhanced Branching). The significance of the EBR1 family expansion on supernumerary chromosomes and whether EBR1 paralogues are functional is currently unknown. EBR1 is found as a single copy in F. graminearum and other fungi but as multiple paralogues in pathogenic F. oxysporum strains. These paralogues exhibit sequence and copy number variation among different host‐specific strains and even between more closely related strains. Relative expression of the EBR1 paralogues depends on growth conditions and on the presence of the single EBR1 gene in the core genome. Deletion of EBR1 in the core genome in different F. oxysporum strains resulted in impaired growth, reduced pathogenicity and slightly reduced biocontrol capacities. To identify genes regulated by EBR1, the transcriptomes of wild‐type and Δebr1 strains were compared for both F. oxysporum and F. graminearum. These studies showed that in both species, EBR1 regulates genes involved in general metabolism as well as virulence.